2021
DOI: 10.3390/ani11010210
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Milk Thistle (Silybum marianum) Seed Cakes on Biochemical Values of Equine Plasma Subjected to Physical Exertion

Abstract: Veterinarians can recommend milk thistle for the treatment of equine liver disease and laminitis. Milk thistle seed cakes were fed in the range of normal feed doses in this study. The milk thistle seed cakes were fed (twice a day) to the experimental group of the horses (n = 5) and biochemical blood markers (TP, Albumin, ALT (alanine transaminase), AST (aspartate transaminase), ALP (alkaline phosphatase), GGT (gamma-glutamyltransferase), Bilirubin, Cholesterol, HDL (high-density lipoprotein), LDL (low-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The renal histological damage protection effect of SMS extract has been demonstrated by Jaggi et al [5]. In addition, plenty of studies have demonstrated that dietary supplementation of SMS extract had no significant effects on the serum creatinine levels in ducks [36], horses [37], and dogs [29]. Therefore, the results of this study indicated that dietary supplementation of SMS extract had no adverse effects on the renal function in weaned piglets.…”
Section: Discussionsupporting
confidence: 61%
“…The renal histological damage protection effect of SMS extract has been demonstrated by Jaggi et al [5]. In addition, plenty of studies have demonstrated that dietary supplementation of SMS extract had no significant effects on the serum creatinine levels in ducks [36], horses [37], and dogs [29]. Therefore, the results of this study indicated that dietary supplementation of SMS extract had no adverse effects on the renal function in weaned piglets.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, in the study of Docklalova et al [ 59 ], sport horses were feed with milk-thistle seed cakes (400 g/day) for 56 days and exposed to heavy physical exercise (2 h of regular combined driving training). The results showed a general positive effect on health of the horses, but significant differences were found in AST, non-esterified fatty acids (NEFA), cortisol, and phosphorus (Pi).…”
Section: Discussionmentioning
confidence: 99%
“…SIL provided by the administration of milk thistle seed cake had a positive effect on horse health and energy metabolism, proven by lower NEFA values, with higher utilization of NEFA during exercise, associated with a faster return of cortisol to the resting values. In another study conducted by Dockalova and colleagues [119], mares were fed with different daily feed doses of milk thistle expeller (100,200,400, and 700 g/d) with an SIL content of 3.4, 6.8, 13.4, and 19.4 g/d, respectively, to evaluate the digestibility of SIL, monitored by HPLC-UV from feces samples. The authors evidenced statistically significant differences on digestibility of flavonolignans, and for ALT and creatinine level.…”
Section: Milk Thistle and Its Derivative Products In Horsesmentioning
confidence: 99%